Higher Order Convergent Newton Type Iterative Methods - Jnawali, Jivandhar (Journal of Nepal Mathematical Society, 2018)
Newton method is one of the most widely used numerical methods for solving nonlinear equations. McDougall and Wotherspoon [Appl. Math. Lett., 29 (2014), 20-25] modified this method in predictor-corrector form and get an order of convergence 1+√2. More on the PDF